Hubungan Penerapan Good Corporate Governance dan Mutu Pelayanan Kesehatan terhadap Kepuasan Pasien Unit Rawat Inap di Rumah Sakit Umum Haji Medan - Yosia Nathaniel E. Halawa; Chrismis Novalinda Ginting; Muhammad Aditya Kurnia (LPPM Hang Tuah Pekanbaru, 2022)
The community needs good health services to fulfill the rights of Indonesian citizens. As health services organizations, hospitals must be able to provide good services. The implementation of health services with integrity, transparency, accountability, and responsiveness requires a system that can integrate all of these components. Hospitals must provide quality health services at affordable prices to increase customer satisfaction and strive to evaluate and capture all opportunities and increase theirs. Competitiveness in an inpatient unit at the Medan Haji General Hospital (RSUHM) North Sumatra Province. The type of research used in this research is quantitative analytics with a cross-sectional design. The sample used in this study was an inpatient unit at the Medan Haji General Hospital (RSUHM) North Sumatra Province, amounting to 100 people. Data analysis using Spearman correlation test and multiple linear regression multivariate analysis. The results showed that there was a significant relationship between all dimensions of the principles of Good Corporate Governance and the quality of health services with patient satisfaction. Through multiple linear regression analysis, it is known that the Responsiveness variable is the most dominant variable in influencing patient satisfaction. Based on these conclusions, the researchers suggest that doctors, nurses, and other officers should improve their services to patients. In addition, researchers also suggest that the results of this study can be used as input for stakeholders in policy-making, especially in the health sector.